INISIASI SISTEM DAN MANAJEMEN DATA PEREKONOMIAN DESA, MELALUI PENGELOLAAN BUM DESA DI PROVINSI JAWA TIMUR - Risanda A Budiantoro; Aulia Prima Kharismaputra; Ahmad Sehabuddin (Jurnal Riset Entrepreneurship, 2023)
The purpose of this study is to analyze the East Java Provincial Government in initiating “Si Langit Bumi” as a form of providing information system services and village economic data management through managing computer-based village-owned enterprises and integrated websites that are easy to access for users. This study uses a business model canvas with secondary data as an analytical tool. The results of the research are in the form of ideal modeling of “Si Langit Bumi”, based on a memorandum of understanding between the stakeholders involved in order to manage information systems and village economic data management to become transparent, accountable, and on target and to make village-owned enterprises in East Java Province more resilient and contribute to the regional economy.